Orbital angular momentum spectrum of antenna vortex beam based on loop integration - Guang Yang (AIP Publishing LLC, 2021)
Due to the divergence characteristics of vortex microwaves, it is difficult to determine orbital angular momentum (OAM) orders through far fields, while the spiral spectrum analysis method based on the area integral of antenna near fields is complicated. In this paper, combined with near-field approximation processing, a spiral spectrum analysis method based on loop integration is proposed. According to the Laguerre–Gaussian vortex beam model, the key parameter estimation formulas suitable for low-order OAM microwave beams are derived, including the position of the reliable observation plane and the size of the annulus area. On this basis, the radius of the integral loop used for the spiral spectrum calculation is provided. Since only field data on the loop are collected in this method, the calculation amount is reduced and the analysis efficiency of the spiral spectrum is greatly improved. Due to the combination of near-field and far-field considerations, this method can fully reflect the spiral spectrum characteristics of antenna vortex waves.